QUALITY MANAGEMENT IN OVERCOMING STUDENT BOREDOM - Ubaidillah, Ubaidillah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The fatigue of learning is a psychological condition characterized by boredom and excessive fatigue, leading to a lack of enthusiasm for engaging in learning activities. If a student loses the desire to learn and motivation for studying, they will become bored with the learning process. The abundance of school assignments makes students feel bored and often neglect their tasks. This journal explores strategies and practices of quality management as an effective approach to address the challenges of student boredom in the education environment. Through Action Research and qualitative analysis, we delve into the implementation of quality-based curriculum, the use of learning technology, and differentiation strategies to create a more dynamic and relevant learning experience. Additionally, the journal discusses the role of parental involvement in decision-making, and psychosocial approaches to strengthen dimensions. The research results indicate that this approach is effective in enhancing student motivation, reducing boredom, and creating a more positive learning environment. Practical implications and recommendations for future research are also discussed.